Vegetation changes of Sundarbans based on Landsat imagery analysis between 1975 and 2006 - Islam, Md. Tariqul (Acta Geographica Debrecina Landscape & Environment series, 2014)
The Sundarbans in Bangladesh and India is the largest single block of tidal halophytic mangrove forest in the world. This forest is threatened by effect of climate change and manmade activities. The aim of this paper is to show changes in vegetation cover of Sundarbans since 1975 using Landsat imagery. Normalized Difference Vegetation Index is applied to quantify and qualify density of vegetation on a patch of land. Estimated land area (excluded water body) of this forest is 66% in Bangladesh, and 34% in India, respectively. Net erosion since 1975 to 2006 is 5.9%. In vicinity of human settlement, areal changes are not observed since 1975. The mangrove forest is decreased by 19.3% due severe tropical cyclone in 1977 and 1988. Moreover, the dense forest is damaged by about 50%. However, more than 25 years is taken by Sundarbans to recover from damage by a severe tropical cyclone. The biodiversity of Sundarbans depends to fresh water flow through it. Therefore, the future of Sundarbans depends to the impact of climate change which has further effect to increasing intensity and frequency of severe tropical cyclone and salinity in water channels in Sundarbans.